To improve ‏communicative competence by expressive and directive speech acts in EFL classroom - Salim, Athmar; Varnosf, Azizollah Dabaghi (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
The Speech acts have been extensively studied as a component of essential communication competence skills. The purpose of this study was to examine speech acts as interlanguage pragmatics with an emphasis on EFL settings.Along with grammatical knowledge, it also includes awareness of cultural standards, social regulations, and the capacity to modify language use according to various contexts. In essence, it's about knowing something rather than merely how to describe it.The Open-ended Discourse Completion Test (DCT) Evaluation Questionnaire and IELTS scores were used in a mixed-methods approach to evaluate learners' pragmatic skills both before and after the intervention. According to the results, students in technologically enhanced settings demonstrated noticeably better speech act performance than those in conventional settings. It was discovered that explicit pragmatics training was beneficial, and the results were influenced by demographic variables such age, gender, and language ability.